2020
DOI: 10.1590/0034-7167-2018-0324
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic diseases and active aging - polypharmacy in control

Abstract: Objectives: To estimate the prevalence of cardiometabolic diseases and their association with polypharmacy in elderly people at the University of the Third Age (Portuguese acronym: UnATI). Methods: A cross-sectional, descriptive, analytical study with 121 elderly patients. The prevalence ratio, Pearson’s Chi-square test and Fisher’s exact test were used as measures of association. Results: At the mean age of 68.3, most elderly had at least one cardiometabolic disease (82.6%), of which hypertension was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
1
0
11
Order By: Relevance
“…Medeiros dos Santos et al demonstrated a common association between antihypertensive and lipid-lowering or antidiabetic drugs [41]. In their study, all polypharmacy cases involved at least one of these combinations [41]. In our study, in addition to lipid-lowering and antidiabetic drugs, antihypertensive medication was frequently associated with antiplatelet agents, proton pump inhibitors, anticoagulants, vitamins and minerals, antianginal agents, and antibiotics.…”
Section: Polypharmacy In Patients With Hypertensionsupporting
confidence: 60%
See 1 more Smart Citation
“…Medeiros dos Santos et al demonstrated a common association between antihypertensive and lipid-lowering or antidiabetic drugs [41]. In their study, all polypharmacy cases involved at least one of these combinations [41]. In our study, in addition to lipid-lowering and antidiabetic drugs, antihypertensive medication was frequently associated with antiplatelet agents, proton pump inhibitors, anticoagulants, vitamins and minerals, antianginal agents, and antibiotics.…”
Section: Polypharmacy In Patients With Hypertensionsupporting
confidence: 60%
“…All these factors significantly increase the risk of polypharmacy [40]. Medeiros dos Santos et al demonstrated a common association between antihypertensive and lipid-lowering or antidiabetic drugs [41]. In their study, all polypharmacy cases involved at least one of these combinations [41].…”
Section: Polypharmacy In Patients With Hypertensionmentioning
confidence: 91%
“…De acordo comSousa et al, (2021) [21], o paciente idoso portador de hipertensão arterial sistêmica possui algumas variáveis que atrapalham a adesão ao seu tratamento medicamentoso, como descuido de tomar a medicação no horário correto, dificuldades financeiras, aspectos sociais e polifarmácia. Dos Santos, Dias e Martins (2021)[22], declaram que, com o envelhecimento, Em concordância com os estudos de [25], em que 78,9% (n=15) dos idosos entrevistados fazem uso da metformina para tratar o diabetes melitos,…”
unclassified
“…Concluiu-se no estudo de [25] que 44,4% (n=12) dos entrevistados fazem associação dos bloqueadores do receptor da angiotensina II com diuréticos para Silva et. al.…”
unclassified
“…idosos (BuiVan et al, 2019;Santos et al, 2020). Entretanto, diverge de estudo realizado em Goiânia com 912 idosos, no qual a prevalência em homens (78,6%) foi maior do que nas mulheres (72,6%) (p= 0,043)(Sousa et al, 2018).…”
unclassified